Work environment and accreditation: analysis by mixed explanatory sequential method - João Lucas Campos de Oliveira; Verusca Soares de Souza; Ana Carolina Simões Pereira; Maria do Carmo Fernandez Lourenço Haddad; Sonia Silva Marcon; Laura Misue Matsuda (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To analyze the - possible - interference of Accreditation in the work environment of the nursing team. Method: Mixed explanatory sequential method study. The first (preponderant) quantitative phase of the research was the application of the Brazilian version of Nursing Work Index Revised (B-NWI-R) to a representative sample (n = 226) of nursing workers from three hospitals, one of them being certificate of excellence by national Accreditation and two unsealed hospitals. After descriptive analysis of the data, it was possible to connect the information, which culminated in the data collection, through interviews (n = 39), of the second (qualitative) stage of the mixed research. The final analysis included the application of inferential statistics and qualitative analysis by the Collective Subject Discourse (DSC), connected in the B-NWI-R dimensions. Results: There was no statistically significant association in the comparisons. However, the results presented better in the certified hospital, ratifying the DSC of this institution. Conclusion: Accreditation did not significantly interfere with nursing staff perception of the work environment.